2022
DOI: 10.1186/s12904-022-00970-z
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study assessing aggressive interventions at the end-of-life among patients with solid metastatic cancer

Abstract: Background Many patients with a solid metastatic cancer are treated aggressively during their last month of life. Using data from a large prospective cohort study of patients with an advanced cancer, we aimed to assess the number and predictors of aggressive interventions during last month of life among patients with solid metastatic cancer and its association with bereaved caregivers’ outcomes. Methods We used data of 345 deceased patients from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 70 publications
0
8
0
2
Order By: Relevance
“…Place of death is often considered an indicator of quality end-of-life care 162 163. It is based on the assumption that home deaths are less intrusive and are associated with lower healthcare costs 164 165.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Place of death is often considered an indicator of quality end-of-life care 162 163. It is based on the assumption that home deaths are less intrusive and are associated with lower healthcare costs 164 165.…”
Section: Discussionmentioning
confidence: 99%
“…Place of death is often considered an indicator of quality end-of-life care. 162 163 It is based on the assumption that home deaths are less intrusive and are associated with lower healthcare costs. 164 165 However, not all patients prefer a home death 155 157 166 and home deaths may not be feasible to achieve in many instances due to practical constraints.…”
Section: Discussionmentioning
confidence: 99%
“…The role of patient preferences for life extension in predicting hospital readmissions has also been overlooked. This is despite studies suggesting that patients who prefer life extending treatments also receive more aggressive treatments 11 . The association between patient preferences for life extension and hospital readmissions may vary by patients' financial situation and healthcare affordability.…”
Section: Introductionmentioning
confidence: 96%
“…Patient and caregiver goals of care are influenced by their characteristics. 17 Previous studies have shown that patients who were married, 18,19 experienced unplanned hospitalizations, 20,21 and faced higher financial difficulties 22 tended to prioritize life extension.…”
Section: Introductionmentioning
confidence: 99%
“…Patient and caregiver goals of care are influenced by their characteristics . Previous studies have shown that patients who were married, experienced unplanned hospitalizations, and faced higher financial difficulties tended to prioritize life extension. Conversely, older patients and those with a correct understanding of their prognosis, higher symptom burden, and greater spiritual well-being were more inclined toward prioritizing symptom management.…”
Section: Introductionmentioning
confidence: 99%